Health amongst former rugby union players: A cross-sectional study of morbidity and health-related quality of life - Davies, M; D Judge, A; Delmestri, A; PT Kemp, S; Stokes, K; Arden, N; Newton, J (Nature Publishing Group, 2017)
In the general population, physical activity is associated with improved health outcomes. However, long-term sports participation may be associated with adverse outcomes, particularly at the elite level. The aims of this study were to assess morbidity and health-related quality of life (HrQoL) amongst former rugby players, compared to an age-standardised general population sample. A cross-sectional study of former elite, male, rugby players (n = 259) was undertaken, and standardised morbidity ratios (SMR) calculated, assessing morbidity prevalence relative to English Longitudinal Study of Aging participants (ELSA, n = 5186). HrQoL, measured using the EQ-5D, was compared to a Health Survey for England (HSE, n = 2981) sample. In SMR analyses of participants aged 50+, diabetes was significantly lower amongst former players, (0.28, 95% CI 0.11–0.66), whereas osteoarthritis (4.00, 95% CI 3.32–4.81), joint replacement (6.02, 95% CI 4.66–7.77), osteoporosis (2.69, 95% CI 1.35–5.38), and anxiety (2.00, 95% CI 1.11–3.61) were significantly higher. More problems in HrQoL were reported amongst former players within the domains of mobility (p < 0.001), self-care (p = 0.041), usual activities (p < 0.001) and pain/discomfort (p < 0.001). Morbidity and HrQoL differ between players and the general population, with higher musculoskeletal morbidity and lower diabetes amongst former players. The magnitude of musculoskeletal morbidity may warrant proactive osteoarthritis management within this population.